Along the Plaza - Henry Kimball Hadley::::::::: (Thiebes-Stierlin Music Co.)
Piano score, 14 p. At head of title: Official St. Louis worlds fair waltz. (1904) At head of title on cover: Official musical publication, Louisiana Purchase Exposition, St Louis, 1904 On cover: Dedicated to the Board of Lady Managers Also on cover is drawing of Festival hall, by Emon Howe Bailey. Biographical sketch and port. of composer on inside front cover. Information on music at the exposition with biographical sketches of George W. Stewart, Manager of the Music Bureau George D. Markham, Chief of the Bureau of Music and Ernest R. Kroeger, Master of Programs, Bureau of Music, on inside back cover. Sculpture Music, by Robert P. Bringhurst, on verso of last leaf. Page 12 is a blank sheet, omitted in file numbering.